Implementasi moderasi islam untuk meningkatkan layanan nikah di Kantor Urusan Agama (KUA) kecamatan Sungai Penuh - Syamsarina Syamsarina; Halim Halim (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the implementation of Islamic moderation in enhancing marriage services at the Religious Affairs Office (Kantor Urusan Agama/KUA) of Sungai Penuh District. Islamic moderation is a crucial principle in public services, including marriage services, to create a balance between Islamic values, compliance with state regulations, and social diversity. This research employs a qualitative descriptive approach using a case study method, involving KUA officials, religious counselors, and prospective married couples as key informants. The findings indicate that Islamic moderation has been implemented in various aspects of marriage services, particularly through premarital counseling, inclusive administrative services, and tolerance-based religious guidance. However, several challenges hinder its implementation, such as a lack of public understanding of Islamic moderation, limited resources at KUA, and difficulties in addressing different religious interpretations. Despite these challenges, the application of Islamic moderation in marriage services has had a positive impact on improving service quality and raising awareness among prospective couples about the importance of building a harmonious household. To strengthen the implementation of Islamic moderation in marriage services, enhancing premarital counseling, improving KUA staff capacity, and utilizing technology in marriage services are necessary.